Early ovarian cancer: our view of the problem - K. I. Zhordania; S. V. Khokhlova (ABV-press, 2014)
The paper considers some pathogenetic aspects of ovarian tumor development, on the basis of which the authors recommend to perform more aggressive chemotherapy in patients with the so-called early stages of ovarian cancer.